2013
DOI: 10.14194/ijmbr.232
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam: A Review of its use in the treatment of epilepsy

Abstract: Background: Levetiracetam is a novel antiepileptic drug. It is marketed worldwide since 2000. Aim: The paper reviewed the mechanism of action, pharmacokinetics, adverse drug reactions, contraindications and uses of levetiracetam in the treatment of various types of epileptic seizures. Methods: Literature searches were done to identify relevant studies. Results: Levetiracetam acts by binding to the synaptic vesicle protein SV2A, thereby modulation of one or more of its actions and ultimately affecting neural ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
(105 reference statements)
0
8
0
1
Order By: Relevance
“…Patients with comorbid psychiatric conditions, headache, and neuropathic pain may also be treated with AEDs for which there are multiple indications for use (e.g., valproate for bipolar disorder and headache and topiramate for headache). Alternatively, some comorbid conditions may be negatively affected by certain AEDs, such as increased or reoccurring psychiatric symptoms after use of levetiracetam [4][5][6][7]. Finally, because of the potential for drug interactions and side effects in older patients, age should be considered when selecting AEDs (e.g., phenytoin and phenobarbital) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with comorbid psychiatric conditions, headache, and neuropathic pain may also be treated with AEDs for which there are multiple indications for use (e.g., valproate for bipolar disorder and headache and topiramate for headache). Alternatively, some comorbid conditions may be negatively affected by certain AEDs, such as increased or reoccurring psychiatric symptoms after use of levetiracetam [4][5][6][7]. Finally, because of the potential for drug interactions and side effects in older patients, age should be considered when selecting AEDs (e.g., phenytoin and phenobarbital) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Seizure control was excellent (seizure-free) in almost all patients treated with levetiracetam. We started AED monotherapy with levetiracetam, a drug we use since the early 2000s that has been shown to be effective for focal and generalized onset seizures [3,[17], [18], [19], [20], [21]], Currently, there is no evidence of levetiracetam interaction with any known drug, especially drugs administered to neuro-oncologic patients, as it does not have deleterious effects on cognition [[22], [23], [24], [25], [26]]. Reasons why patients with seizures did not start treatment on levetiracetam (25%) were: 1) accessibility to medication; 2) poor health and death before treatment initiation; and 3) transfer of care to other medical centers.…”
Section: Discussionmentioning
confidence: 99%
“…The result of the study shows that PHT and LEV showed equal efficacy in prevention of seizures after TBI. Swaroop et al, (2013); conducted a study based on Levetiracetam: A Review of its use in the treatment of epilepsy. Levetiracetam is a novel antiepileptic drug.…”
Section: Introductionmentioning
confidence: 99%